Let them all talk [videorecording (DVD)] - Streep, Meryl; Bergen, Candice, 1946-; Chan, Gemma, 1982-; Hedges, Lucas, 1996-; Wiest, Dianne (Warner Bros. Entertainment Inc., 2022)
The story of a famous author who takes a journey with some old friends to have some fun and heal old wounds. Her nephew comes along to manage the women, along with her literary agent, who is impatient to find out about her next book.